The "Service" model of the competences of the municipal employee as the basis of vocational training: Russian experience - Martynova, Svetlana E. (Procedia - Social and Behavioral Sciences)
Competences of the municipal employee are considered in a context of the “service” concept of the public and municipal administration. The results of the sociological researches reflecting estimates and expectations are the basis for a model of the competences, connected with local authorities. In the article the technology and the results of the selection of the applicants for a reserve for the municipal positions are presented on the basis of the offered model of the competences also. From the point of view of the purposes of the vocational training the offered model of the competences can act as a basis for a formation of the curriculum.